2022
DOI: 10.1021/acsomega.2c03804
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure Characteristics and Affecting Factors of Shale in the First Member of the Qingshankou Formation in the Gulong Sag, Songliao Basin

Abstract: A major historical breakthrough has been made in the exploration of the GK (the first member of the Qingshankou Formation (K2qn 1 ), Gulong Sag) shale oil of the Songliao Basin. However, few reports have been reported on the pore structure characteristics of this large-scale lacustrine medium−high maturity shale. In addition, the difference between the pore structure characteristics of the GK shale and medium−low maturity marine/ continental shale is unknown, and the affecting factors of pore development are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Minerals and OM are the two major solid components of shale. Some scholars argue that minerals and OM play important roles in the pore structure. ,,, Hard minerals, such as quartz and feldspar, can form interparticle pores with other constituents (minerals, fossils, and OM) and pressure shadows that resist compaction to protect primary pores, and some hard minerals (e.g., anorthite) can also form intraparticle pores after dissolving . In addition, clay minerals can form cleavage-plane pores and pores within clay flocculates .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Minerals and OM are the two major solid components of shale. Some scholars argue that minerals and OM play important roles in the pore structure. ,,, Hard minerals, such as quartz and feldspar, can form interparticle pores with other constituents (minerals, fossils, and OM) and pressure shadows that resist compaction to protect primary pores, and some hard minerals (e.g., anorthite) can also form intraparticle pores after dissolving . In addition, clay minerals can form cleavage-plane pores and pores within clay flocculates .…”
Section: Resultsmentioning
confidence: 99%
“…The four oil shale-bearing formations in Jilin Province are in the immature to low-maturity stages of thermal evolution, with the most mature formation being the Qingshankou Formation ( R o ∼ 0.76%). ,, Moreover, Lu et al observed that only rare OM pores occur in the Qingshankou Formation among these four formations by using Ar ion polishing and FE-SEM imaging techniques. Thus, it is difficult to establish the relationship between pore structure and OM using total organic carbon (TOC) data, as other scholars have completed previously. ,,,,,, Therefore in this section, we mainly discuss the influences of mineral composition on pore structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation pressure index (P index ) is generally greater than 1.2, reaching a maximum of 1.57 (Cui et al, 2020;He et al, 2021). The density and viscosity of crude oil are generally less than 0.84 g/cm 3 and 0.8 mPa• s, respectively (Cui et al, 2020;Sun et al, 2021;He et al, 2022). The gas-oil ratio is high and the production gas-oil ratio of the GYYP-1 well located in the deep part of the sag exceeds 400 m 3 /m 3 (Sun, 2020;Sun et al, 2021).…”
Section: Geological Settingmentioning
confidence: 99%
“…The Upper Cretaceous Qingshankou Formation is the main source rock and reservoir of shale oil in the Gulong Sag, thus is also the important exploration target for shale oil in the Gulong Sag at the present. Due to its significance in Gulong shale oil development, tremendous efforts have been made to elucidate its petrological properties (Wang et al, 2021b), lithofacies (Liu et al, 2018), sedimentary background (Jin et al, 2020), diagenetic-pore evolution (Feng et al, 2021;Shao et al, 2021), shale oil enrichment status (Zhang et al, 2021a;He et al, 2022), controlling factors of shale enrichment and shale oil quality (Sun et al, 2021). However, research on the enrichment-influencing factors of retained hydrocarbons remains inadequate.…”
Section: Introductionmentioning
confidence: 99%